Clinical Outcomes after Surgery for Linitis Plastica of the Stomach: Analysis of a Population Cancer Registry. Issue 1 (January 2017) - Chang, James M.; Lara, Kelly A.; Gray, Richard J.; Pockaj, Barbara A.; Wasif, Nabil
Linitis plastica (LP), a subset of gastric adenocarcinoma (GA), has been considered as a fatal disease with few management options. Little evidence has been reported regarding the role for surgical therapy in treating LP. A retrospective review of GA patients with LP from the surveillance, epidemiology, and end results database (2004–2009) was performed. 29, 440 patients with GA were identified, of whom 948 (3.2%) had LP. After matching for American Joint Commission on Cancer (AJCC) stage, LP patients had significantly worse 5-year disease specific survival (DSS) compared with GA (6 vs 34%, P < 0.001). For potentially resectable LP patients (i.e., stage I–III), 5-year DSS was 0 per cent for no treatment and for radiation therapy alone, 18 per cent for both and surgery and radiation, and 20 per cent for surgery alone(P < 0.001). LP is a marker of poor survival in patients with GA. However, surgical resection provides the best oncologic outcomes in these patients with a 20 per cent 5-year DSS in patients with loco-regional disease.